WEF nexus narratives: toward sustainable resource security - Mabhaudhi, Tafadzwanashe; Senzanje, A.; Modi, A.; Jewitt, G.; Massawe, F. (Elsevier, 2022)
The water–food–energy (WEF) nexus narratives is a collection of expert inputs on the concepts, analytical tools and case studies, and key developments on the importance and applicability of the WEF nexus as a transformative and circular approach. This chapter provides a detailed summary of each chapter, providing the reader with what has been achieved through the WEF nexus application. The chapters provide practical applications of integrated resource management and the pathways toward sustainable development. The main subjects of discussion include data availability, modeling tools, indices development, and metrics and their application across multiple spatiotemporal scales.